Research Status of Electrolytic Preparation of Rare Earth Metals and Alloys in Fluoride Molten Salt System: A Mini Review of China - Chunfa Liao; Lianghua Que; Zanhui Fu; Pan Deng; Alin Li; Xu Wang; Shumei Chen (Metals, 2024)
China’s rare earth reserves and consumption are the highest in the world. Rare earth metals and alloys play a pivotal role in the domains of permanent magnetic materials, hydrogen storage materials, luminescent materials, abrasive materials, etc. The molten salt electrolysis process is the most widely used method for producing light rare earth metals and alloys in China, with distinct advantages such as continuous production and short process flow. This article focuses on the process technology of preparing rare earth metals and alloys by electrolyzing rare earth oxides in fluoride systems. This article summarizes the effects of process parameters such as cathode and anode structures, electrolysis temperature, and current density on the direct recovery and current efficiency of the preparation of light rare earth metals (La, Ce, Pr, Nd), RE–Mg (RE for rare earth) alloys, RE–Al alloys, RE–Ni alloys, and other rare earth alloys. Meanwhile, the disadvantages of the electrolytic cells and electrode configurations that are currently used in industrial production are discussed. Accordingly, the future prospects of molten salt electrolysis technology in the preparation of rare earth metals and alloys are clarified.